Unmethylated CpG motif-containing genomic DNA fragments of bacillus calmette-guerin improves immune response towards a DNA vaccine for COVID-19. Issue 41 (1st October 2021) - Zhou, Zehua; Zhang, Xinyu; Li, Qianqian; Fu, Lili; Wang, Meiyu; Liu, Shuo; Wu, Jiajing; Nie, Jianhui; Zhang, Li; Zhao, Chenyan; Jiang, Fei; An, Yimeng; et al.
Abstract: The development of an effective vaccine to control the global coronavirus disease-2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus- 2 (SARS-CoV-2) is of utmost importance. In this study, a synthetic DNA-based vaccine candidate, known as pSV10-SARS-CoV-2, expressing the SARS-CoV-2 spike protein was designed and tested in 39 BALB/c mice with BC01, an adjuvant derived from unmethylated CpG motif-containing DNA fragments from the Bacillus Calmette-Guerin genome. Mice vaccinated with pSV10-SARS-CoV-2 with BC01 produced early neutralizing antibodies and developed stronger humoral and cellular immune responses compared to mice that received the DNA vaccine only. Moreover, sera from mice vaccinated with pSV10-SARS-CoV-2 with BC01 can neutralize certain variants, including 614G, 614G + 472 V, 452R, 483A, 501Y.V2, and B.1.1.7. The results of this study demonstrate that the addition of BC01 to a DNA-vaccine for COVID-19 could elicit more effective neutralizing antibody titers for disease prevention.